Mountain Resort - SABRI, KHAWLA (My University, 2022)
My project is a tourist mountain resort in the village of Balaa-Rasheen - East Tulkarm district - the project area is 65 acres - the site I chose is distinguished by its strategy and its distinct view towards the west on the occupied Palestinian coast. The main building that contains the administration, waiting, restaurants, spa and Swimming pools and other distinct activities, with the nature of the mountain and the town, as well as in sequence with the chalets, which amount to 23 chalets, in a streamlined direction towards the view in a different way that mimics the old houses in Bala’a. cube house- shape L house The project derives its idea and distinction from the needs of the community and the site at the same time, which is to preserve the value of the Palestinian lands and preserve the memory of the site, in addition to highlighting the beauty of the nature of our dear country Palestine with its villages, cities and all its details. We are also in a time when we need psychological comfort and self-entertainment for the whole family. The resort is the best option that includes among its parts all the concepts of comfort.